Analysis of Biogenic Amines in fish by using High Performance Liquid Chromatography - Nur Idatul Diana, bt Ahmad Zaki (Universiti Malaysia Sarawak (UNIMAS), 2015)
Biogenic amines (BAs) are organic basis formed in food by microorganisms through enzymatic decarboxylation of amino acid, non volatile and heat stable. Biogenic amine can be found in several of food especially food that inappropriate handle and stored scombroid fish like tuna. The aim of this study was for the verification of an high performance liquid chromatography (HPLC) method for the determination of biogenic amines in fish. The implementation of the method included the optimization of sample preparation, HPLC analysis and data evaluation. Thereafter, the method performance was verified to demonstrate that the results obtained were consistent, correct and satisfactory for analysis of biogenic amines in fish. Separation of biogenic amine was achieved on a Purospher® STAR column with gradient elution system coupled with a UV detector (198 nm). A mixture of standard biogenic amines consist of tyramine, cadaverine and histamine were used for the verification test such as linearity, limit of detection, limit of quantification, accuracy, precison and recovery. The calibration curves for biogenic amines are linear from the concentration of 10 ppm until 75 ppm and linearity coefficients (r2) >0.900 for tyramine and histamine. Relative standard deviation (RSD) for biogenic amines <10% which are 4.74%, 5.15% and 5.53% for tyramine, cadaverine and histamine. The recovery in the concentration of tyramine and cadaverine are 86% and 95%, respectively.